Asset Price Inflation in the 1980's : A Flow of Funds Perspective - Schinasi, Garry; Hargraves, Monica; Weisbrod, Steven (Washington, D.C. : International Monetary Fund, 1993)
This paper examines how and why financial resources were channeled almost exclusively to specific asset markets in Japan, the United Kingdom, and the United States in the late 1980s. A decline in demand for funds by traditional borrowers, and a shift by savers from banks toward indirect securities investments were critical factors in all three cases. Until intermediaries and investors learned to evaluate new opportunities, funds were recycled in certain asset markets. The pressures on Japanese asset markets were particularly intense because of the size of Japan's domestic saving relative to traditional domestic investment opportunities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet